Mengatasi Pergaulan Bebas Dikalangan Masyarakat Ilmiah - Gilang Rama Maulana (Universitas Negeri Makassar, 2020)
This journal aims to explain the negative effects of promiscuti and find out the influence of promiscuity in the family, scho and community. In this journal contains the definition of promiscuity, types of promiscuity, the danger of promiscuity, the law of promiscuity according to religion and state, the solution or prevention of promiscuity. The benefit of this journal is to increase the community's knowledge and insight about promiscuity and create a good community environment.